PENGELUARAN BELANJA MODAL PEMERINTAH DAN KREDIT MODAL KERJA TERHADAP PERTUMBUHAN EKONOMI PROVINSI DI PULAU SUMATERA - ana, Sri Mardiana (Fakultas Ekonomi Universitas IBA, 2019)
The purpose of this study was to analyze the development of government capital and working capital loans on economic growth in Sumatra in 2010-2016. This study uses secondary data in the form of panel data and analyzed using descriptive and quantitative methods. The result of the coefficient of determination is 0.905390 which shows economic growth by government capital expenditure and working capital credit by 90% while the remaining 10% is needed by other factors outside the model. Based on the t-test partial test, government capital expenditure and working capital credit are significant to the economic growth of the province in Sumatra.